SOIL SPECTRAL MAPPING AND ITS CORRELATION WITH THE TRADITIONAL METHODOLOGY - Chicati, Marcelo Luiz; Nanni, Marcos Rafael; Cézar, Everson; Oliveira, Roney Berti de; Chicati, Mônica Sacioto (Boletim de Ciências Geodésicas, 2018)
The use of remote sensing is increasing in agriculture and this raises questions about its efficiency over other usual methods. Thus, the purposes of this study were to compare methodologies for soil mapping, using field samplings and spectral data (from laboratory and from a simulated Landsat-TM), and to estimate their correlation. The soil samples were collected in a wetland with a great variety of soil classes. The distribution of soil classes in the maps was based on independence analysis by the Chi-square. Ten soil classes were determined in the study area, 6 in the first category level. The map of laboratory spectral data showed low correlation with conventional data. The map of spectral data that simulated wavelenghts corresponding the spectral bands of Landsat-TM sensor showed the same behavior of the previous map, with lower correlation with the conventional data. Thus, we verified that the mapping of paddy soils with spectral data shows low correlation with conventional data, however, still rather positive.